La Cour internationale de Justice comme instrument de la paix par le droit - Ros, Nathalie (Études internationales, 1994)
The maintenance of international peace and security is the primary purpose of the United Nations and the effective function of the ICJ is obviously to contribute to it. Now that 50years have passed since the foundation of this Court and while the Bosnian case is pending, the question of the effectiveness of its judicial function inevitably arises: in practice, it often suffers from the lack of political will of the sovereign States. But thanks to its contribution to the development of international law, the ICJ indirectly plays an effective role in the cause of world peace : it exercises a function of "normative supply", implied and derived from the primary function of the principal judicial organ of the United Nations.